Penyuluhan Stimulasi Tumbuh Kembang Bayi di Puskesmas Cijeungjing - Lusi Lestari; Heni Heryani; Sri Utami Asmarani (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Infancy is a golden period in a child's life, marked by rapid and significant physical growth and motor, cognitive, language, and social-emotional development. Infant development and growth are interrelated processes that greatly determine the quality of human resources in the future. Infancy, especially between 0 and 12 months, is called the golden period because brain development is rapid during this period. Babies need appropriate and continuous stimulation, a safe environment, and adequate nutrition. One important external factor that can affect the optimal growth and development of children is stimulation. Lack of stimulation in early life can cause delays in children's motor, language, cognitive, and social-emotional development. Objective: The purpose of this community service activity is to increase mothers' knowledge and understanding of the importance of stimulating the growth and development of babies aged 0-12 months. Method: The method used in this activity was counseling in the form of interactive lectures. Result: The results of Community Service show an increase in knowledge of 20 points compared to the pre-test average score, which is equivalent to an increase of 33.33% in counseling on child growth and development. This increase shows that counseling with interactive lectures is effective in increasing participants' knowledge. Conclusion: Community service activities in the form of counseling accompanied by interactive lectures have been proven to increase mothers' knowledge and understanding of the importance of stimulating the growth and development of babies aged 0-12 months.